2000
DOI: 10.1080/713676888
|View full text |Cite
|
Sign up to set email alerts
|

Associate Teachers in Pre-service Education: Clarifying and enhancing their role

Abstract: The research literature indicates lack of clarity and agreement about the role of 'associate teachers'-teachers who supervise teacher education students during their practicum. This study of a group of associate teachers revealed that they found their role satisfying and gave student teachers a considerable amount of support, feedback and direction. However, they often seemed to be rather 'tough' on the student teachers, limiting their freedom to innovate, giving them a very heavy workload and generating in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
11

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(93 citation statements)
references
References 5 publications
2
80
0
11
Order By: Relevance
“…Some studies suggest, for example, that it can result in the promotion and reproduction of conventional norms and practices, which render mentees unable to consolidate or develop their knowledge and use of alternative and more challenging (both for the beginner teacher and to the status quo) methodologies, such as 'progressive' and learner-centred approaches (Feiman-Nemser et al, 1993;Ling, 2009). Others have found that mentoring can have harmful effects on mentees' wellbeing, with studies suggesting that in some cases the work of mentors has damaged beginning teachers' self-esteem, caused anxiety and stress, and contributed to mentees' decisions to leave the profession (Beck and Kosnick, 2000;Maguire, 2001). …”
Section: Benefits and Limitations Of Mentoring In Actionmentioning
confidence: 99%
“…Some studies suggest, for example, that it can result in the promotion and reproduction of conventional norms and practices, which render mentees unable to consolidate or develop their knowledge and use of alternative and more challenging (both for the beginner teacher and to the status quo) methodologies, such as 'progressive' and learner-centred approaches (Feiman-Nemser et al, 1993;Ling, 2009). Others have found that mentoring can have harmful effects on mentees' wellbeing, with studies suggesting that in some cases the work of mentors has damaged beginning teachers' self-esteem, caused anxiety and stress, and contributed to mentees' decisions to leave the profession (Beck and Kosnick, 2000;Maguire, 2001). …”
Section: Benefits and Limitations Of Mentoring In Actionmentioning
confidence: 99%
“…The important role of the university practicum advisor as a facilitator, personal confidante, and trusted guide is viewed as a key element in the ecological transitions that take place during the teaching practice and also as a vital source of emotional support and guide of the learning to teach process (Caires and Almeida, 2005;Hawkey, 1997;Beck and Kosnik, 2000).…”
Section: ) Research Question 2: Mentorship Supportmentioning
confidence: 99%
“…On the other hand, distant relationships between mentor and mentees hinder such positive outcomes (Izadinia 2015, Beck & Kosnik 2000. In the present study, this scenario was reflected through Nadya's brief experience working with Mark as well as Hafiz's unpleasant experience witnessing Patrick losing his temper during TPD workshop.…”
Section: Approachable Versus Intimidatingmentioning
confidence: 77%